Notas sobre el epíteto a partir del valor epitético de los adjetivos compuestos de la épica arcaica griega - Plaza Picón, Francisca del Mar; Batista Rodríguez, José Juan, 1959- (1991)
We deal with the epithetic value of homeric compound adjectives. In fact, from a linguistic point of view the epithetic value must be considered as belonging to performance (i.e. the saussurean parole), because it does only appear in the development of discours.
Keywords: Filología; Poesía épica; Literatura griega